Tracheal Anatomy of the Anatidae and its taxonomic significance - Johnsgard, Paul A (Wildfowl, 1961)
Tracheal and syringeal variations in waterfowl are summarized, based on a tracheal collection representing 84 out of the 143 species of Anatidae. Twenty seven species are illustrated with drawings, and photographs of 24 species are also included, comprising 29 of the 43 genera of Anatidae. The following major points are made: 1. The Magpie Goose (Anseranas semipalmata) is unique in its externally convoluted trachea, but the syrinx is small and simple in both sexes. 2. Species of the subfamily Anserinae have symmetrical tracheae in both sexes, which either lack bullae (Anserini) or have symmetrical bullae which are larger in males than in females (Dendrocygnini). 3. The Coscoroba Swan (Coscoroba coscoroba) and the Cereopsis Goose (Cereopsis novaehollandiae) have tracheae of the Anserini type, and the Freckled Duck (Stictonetta naevosa) has an extremely simple and primitive type of trachea and syrinx in both sexes. 4. Species of the subfamily Anatinae exhibit sexual dimorphism in the syrinx, and males of most species except stiff-tails (Oxyurini) possess asymmetrically enlarged syrinxes (bullae). 5. Enlargements of the tracheal tubes of male Anatinae occur in a few dabbling ducks (Anatini), most of the pochards (Aythyini) and most sea ducks (Mergini). Tracheal air sacs occur in some stiff-tails, and extra-tracheal sound production is also typical of this group. 6. Although males of most Anatinae possess entirely osseous bullae, partially membranaceous (fenestrated) bullae are found in all pochards and most sea ducks. The Marbled Teal (Marmaronetta angustirostris) and Pink-headed Duck (Rhodonessa caryophyllacea) also possess fenestrated bullae which are intermediate between the dabbling duck and pochard types. 7. The sea ducks exhibit the greatest variation in shape and structure of male tracheae, and specializations of the bronchi, tracheal tube, and musculature are frequent. The tribal separation of the eiders on the basis of their tracheal anatomy is not justified.